THE ONLINE CULINARY BUSINESS OF ETHNIC FOOD OF NORTH SUMATRA - Saiful Anwar Matondang, Siti Rahma ,Tashliyah Haramain (International Journal of Advanced Science and Technology, 2020)
This research paper is to find the online culinary business model in North Sumatra Province of Indonesia.